Classifying Car Owners in Latent Psychographic Profiles. Issue 7 (July 2021) - von Behren, Sascha; Bönisch, Lisa; Vallée, Jan; Vortisch, Peter
Policy makers in urban areas are subjected to increasing pressure to find sustainable solutions to congestion and transportation. A detailed understanding of the motivations of car owners is required to enable the development of policies that are both socially fair and take effective measures. The objective of this study is to provide a more granular differentiation of car owners using psychographic profiles in three basic dimensions (privacy, autonomy, and car excitement). These profiles are also examined in relation to general travel behavior in everyday and long-distance travel. Data was collected in Munich and Berlin (Germany) and a latent class analysis was applied to segment respondents into latent profile classes. On this basis, six different profile classes were identified. In addition to the Car Independents profile class which does not have strong orientations toward the car, several profile classes were also identified with high concerns about "privacy" in relation to social distances in public transit. The information and analysis presented enables a deeper understanding of the motivations of the different target profile classes and discusses the need for tailored, socially fair measures to reduce car ownership and use within these groups.